Sharp separation of C2/C3 hydrocarbon mixtures by zeolitic imidazolate framework-8 (ZIF-8) membranes synthesized in aqueous solutions - Pan, Yichang; Lai, Zhiping (Chemical communications (Cambridge, England), 2011)
Exceptional high quality ZIF-8 membranes prepared through a novel seeded growth method in aqueous solutions at near room temperature exhibit excellent separation performance for C2/C3 hydrocarbon mixtures. The separation factors for mixtures of ethane/propane, ethylene/propylene and ethylene/propane are ∼80, ∼10 and ∼167, respectively.